Carol at Brush Road House - unknown:::Creator::::::::::::
Carol Steinbeck standing between two unidentified women with her father Wilbur Henning on the far left at the Brush Road House. The Steinbecks lived here from 1938-1940. Hard copy in 25cm by 17,5cm scrapbook